Efficacy and safety of hyperbaric oxygen therapy for Parkinson’s disease with cognitive dysfunction: protocol for a systematic review and meta-analysis - Weiqiang Tan; Zhaoquan Pan; Fengxi Xie (BMJ Open)
Introduction The presence of cognitive dysfunction notably affects the quality of life in individuals diagnosed with Parkinson’s disease (PD) and is often recognised as a non-motor symptom. Comprehensive studies have shown the possible advantages of hyperbaric oxygen therapy (HBOT) in alleviating cognitive deficits in these individuals. This systematic review aims to investigate the practicality of incorporating HBOT within a more extensive therapeutic framework for PD, with a specific focus on cognitive symptoms.Methods and analysis A comprehensive literature review will be conducted utilising various databases such as PubMed and Cochrane Library and so on. The duration of the search will encompass the entire timeline from the initiation of each database up to 1 April 2024. This investigation seeks to uncover randomised controlled trials that explore the efficacy and safety of HBOT in patients with PD who are facing cognitive impairments. The authors' autonomous screening and extraction of data will facilitate the attainment of impartial results. The assessment of possible biases will be conducted using the Cochrane risk-of-bias tool, while statistical analyses will be executed with RevMan V.5.3 and Stata V.15.0.Ethics and dissemination As this review synthesises and evaluates previously conducted studies, the requirement for ethical approval is not applicable. The findings from this review will be shared via academic publications, comprehensive reports and presentations at pertinent conferences.PROSPERO registration number CRD42024504763